Peran Orang Tua Karir dalam Mengembangkan Karakter Religiusitas Anak - Aam Amaliyah (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2020)
The role of parents in education is something that is very important to determine the success of their children's education. Between the role of parents in developing the character of children's religiosity that need to be considered in a child's moral development is mutually sustainable. The attitude of parents must be in accordance with what is taught to children. One of the roles of parents described above is as a motivator or motivator. Motivation in question can be in the form of encouragement to learn. At the time of learning sometimes the child will experience difficulties and decreased enthusiasm. Parents must provide encouragement so that children are more enthusiastic in learning and able to overcome difficulties. Religious character is a human character that always relies on all aspects of life to religion. Making religion a guide and role model in every speech, attitude, and deed, obeying the commands of God and avoiding the prohibition, if we refer to Pancasila, it clearly states that Indonesian people must believe in God Almighty with the consequences of carrying out all the teachings of their religion.